Power control for successive interference cancellation algorithm based on game theory - Song-hua HU; Jian-jun ZHANG; Yang LU; Bin LIU; Jiang-hong HAN (Tongxin xuebao)
It was proved that implementation of successive interference cancellation could improve network throughput in wireless networks,while in order to maximize network throughput,it was a NP-Hard problem that how to control transmission power when successive interference cancellation was used in wireless networks.A non-cooperative game theory is proposed to solve power control between wireless nodes for successive interference cancellation,in which non-cooperative game theory model is proposed and Nash equilibrium is analyzed,and also the proposed algorithm can ob-tain good network throughput than others,simulations validate the results and demonstrate the superiority of the algorithm.